Ruptured Cornual Ectopic Pregnancy Mimics as Acute Retention of Urine: A Case Report - Guruparan, K.; Hemabala, R. (Cureus, 2025)
Cornual ectopic pregnancy is a rare entity of extrauterine pregnancies and once ruptured, it is associated with high maternal morbidity and mortality. Most of the extrauterine pregnancies are detected with early pregnancy ultrasound scan, but there are diagnostic difficulties in the early detection of cornual ectopic pregnancy. Early recognition of unruptured cornual ectopic and interventions are associated with better outcomes. We report a case of successfully managed ruptured cornual ectopic pregnancy, which presented as acute retention of urine to the emergency unit at the Teaching Hospital, Jaffna.
Keywords: Ectopic pregnancy; En masse lesion; Ruptured cornual ectopic; Unusual presentation; Urinary retention